PENGARUSUTAMAAN GENDER DALAM PENDIDIKAN PESANTREN: KAJIAN FEMINISME ISLAM - Masthuriyah Sa’dan (Jurnal Harkat : Media Komunikasi Gender, 2018)
Abstract. Exit of the Beijing Platform For Action (BPFA) on gender equality mainstreaming was incorporated into development policy during the fourth world women's conference in Beijing in 1995 so Abdurrahman Wahid declared Presidential Instruction number 19 December 2000. 9 of 2000 on gender mainstreaming in national development. This is where the islamic boarding school  is required to be able to respond to the dynamics of the era along with the development of modernization and globalization, so that islamic boarding school  can answer the issue of gender equality discourse that goes into the boarding booths. This paper wants to answer how the strategy and implementation of  Gender Mainstreaming in islamic boarding school  education. This review is literature review using feminist approach and gender analysis in Islam. After the review, the authors found that the strategy for realizing gender mainstreaming in islamic boarding school  education is to re-design the gender perspective teaching curriculum and the implementation of Gender Mainstreaming is through the main stakeholders of islamic boarding school  namely Kyai, Nyai, Ustadzah and ustadz.Abstrak. Dikeluarkannya Beijing Platform For Action (BPFA) tentang gender mainstreaming (PUG) kesetaraan gender masuk dalam kebijakan pembangunan pada saat konferensi perempuan dunia keempat di Beijing tahun 1995 sehingga Presiden Abdurrahman Wahid pada tanggal 19 desember 2000 mengeluarkan Instruksi Presiden (Inpres) No. 9 Tahun 2000 tentang pengarusutamaan gender dalam pembangunan nasional. Disinilah pesantren dituntut untuk mampu merespon dinamika zaman seiring berkembangnya arus modernisasi dan globalisasi, sehingga pesantren mampu menjawab persoalan wacana kesetaraan gender yang masuk ke dalam bilik-bilik pesantren. Tulisan ini ingin menjawab bagaimana strategi dan implementasi PUG dalam pendidikan pesantren. Kajian ini adalah kajian pustaka dengan menggunakan pendekatan feminis dan analisa gender dalam Islam. Setelah dilakukan kajian, penulis menemukan bahwa strategi untuk mewujudkan PUG dalam pendidikan pesantren adalah melakukan re-desain kurikulum pengajaran berprespektif gender dan implementasi PUG adalah melalui pemangku utama pesantren yaitu Kyai, Nyai, Ustadzah dan ustadz.